THE INFLUENCE OF QUALITY ON THE STUDENTS’ DECISION IN CHOOSING VOCATIONAL HIGH SCHOOLS IN WEST JAKARTA - Susanti Susanti; Fadilah Fadilah; Rachmat Setiyadi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This research was conducted to determine the influence of quality on students’ decision in choosing a Vocational High School in West Jakarta. This study compares the two schools; they are 53 State Vocational School (SMKN 53) and Telkom Vocational High School (SMK Telkom), where the two schools are the schools under the guidance of the automotive and the telecommunications industry. Samples taken from the two schools were 65 people using the simple random sampling method. Data collection was carried out by distributing questionnaires using a Likert scale 5. The analysis technique used was path analysis. Hypothesis testing techniques using structure equation model (SEM) analysis with smartPLS statistical applications. The results of the research on SMKN 53 students showed that quality had a significant effect on choosing decisions, as well as on SMK Telkom students which quality had a significant effect on choosing decisions.